Sound and heat insulation light building material and its preparation method
Patent Information
- Application Number
- CN202610237201.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-02-28
- Publication Date
- 2026-10-20
- Estimated Expiration
- 2046-02-28
AI Technical Summary
然而,传统发泡剂受限于泡沫稳定性差及泌水率高,导致基体微观结构缺陷,难以实现力学强度与隔热性能的协同优化,且现有泡沫混凝土普遍存在强度低、易开裂、易吸水等问题,制约其在高标准建筑中的推广应用
本发明利用油酸分子上的羧基与纳米氧化铝表面的羟基发生酯化反应形成化学键合,这种键合将疏水基团接枝到纳米氧化铝颗粒表面,制备得到疏水纳米氧化铝,然后通过皮克林乳液法进行乳化后,氢氧化钠诱导的皂化反应选择性解离疏水纳米氧化铝的化学键合,实现单侧油酸分子脱附,制备得到具有两亲性的改性纳米氧化铝,并采用十二烷基硫酸钠作为发泡剂,羟丙基甲基纤维素、改性纳米氧化铝和纳米二氧化硅作为稳泡剂,其中改性纳米氧化铝颗粒凭借两亲特性赋予其卓越的界面锚定能力,可在气-液界面形成致密吸附层,通过库仑相互作用与十二烷基硫酸钠协同构筑复合界面膜,羟丙基甲基纤维素经氢键与范德华力定向排列形成次级屏障,富含羟基的纳米二氧化硅颗粒则通过静电吸附与十二烷基硫酸钠结合构建第三层防护壳,从而形成具有多壁核壳结构的超稳定泡沫剂,将该泡沫剂引入至泡沫混凝土中,基于应力分散机制与闭孔隔热效应,实现了建筑材料力学-热学协同优化。
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention belongs to the field of building materials technology, specifically relating to a sound-insulating and heat-insulating lightweight building material and its preparation method. Background Technology
[0002] With the rapid development of the construction industry, the quality and performance of building materials play a crucial role in the safety and durability of building projects. Foamed concrete, with its lightweight, high strength, economic efficiency, environmental friendliness, and excellent thermal performance, has become a key material in the green building materials system. This material demonstrates significant engineering application value by reducing the building's life cycle. However, traditional foaming agents are limited by poor foam stability and high bleeding rates, leading to microstructural defects in the matrix and making it difficult to achieve synergistic optimization of mechanical strength and thermal insulation performance. Furthermore, existing foamed concrete generally suffers from low strength, easy cracking, and high water absorption, hindering its widespread application in high-standard buildings. Summary of the Invention
[0003] To address the shortcomings mentioned in the background art, the present invention aims to provide a sound-insulating and heat-insulating lightweight building material and its preparation method. By adding foaming agents and modified composite filler-based water-reducing agents, the prepared lightweight building material has high compressive strength and flexural strength, low water absorption, and good heat insulation performance.
[0004] The objective of this invention can be achieved through the following technical solutions: A sound-insulating and heat-insulating lightweight building material comprises the following raw materials in parts by weight: 100 parts cement, 12-25 parts fly ash, 5-10 parts river sand, 5-10 parts quartz sand, 4-7 parts foaming agent, 1-5 parts modified composite filler-based water-reducing agent, and 45-60 parts deionized water. The foaming agent is made using sodium dodecyl sulfate as a foaming agent and hydroxypropyl methylcellulose, modified nano-alumina, and nano-silica as foam stabilizers. The modified nano-alumina is prepared by esterification of oleic acid with nano-alumina to form chemical bonds, resulting in hydrophobic nano-alumina. After emulsification using the Pickering emulsion method, the chemical bonds of the hydrophobic nano-alumina are selectively dissociated by a sodium hydroxide-induced saponification reaction, achieving desorption of oleic acid molecules on one side. The modified composite filler-based water-reducing agent is prepared by in-situ esterification modification of the composite filler using isopentenyl alcohol polyoxyethylene ether, followed by free radical copolymerization of the prepared modified composite filler with acrylic acid; the composite filler is prepared by oxidizing carbon fibers with concentrated sulfuric acid and concentrated nitric acid to prepare oxidized carbon fibers, followed by grafting graphene oxide and oxidized carbon fibers using 3-aminopropyltriethoxysilane as a "bridging agent".
[0005] Preferably, the cement is P·O42.5 grade ordinary Portland cement; the fineness modulus of the river sand is between 2.4 and 2.8; and the particle size of the quartz sand is 100 to 210 µm.
[0006] Preferably, the preparation of the foaming agent includes the following steps: Modified nano-alumina, nano-silica, and sodium dodecyl sulfate were added to deionized water and sonicated at room temperature for 30 min to obtain a mixture. Hydroxypropyl methylcellulose was dissolved in deionized water and stirred at 500 rpm for 30 min at 50 °C. The solution was then added to the mixture, and calcium hydroxide was added to adjust the pH of the system to 9. The mixture was stirred at 500 rpm for 2 h to obtain a foaming agent solution. The foaming agent solution was then allowed to stand at room temperature for 24 h, and a foaming machine was used to generate a foaming agent using compressed air.
[0007] Preferably, the mass ratio of the modified nano-alumina, nano-silica, sodium dodecyl sulfate, and hydroxypropyl methylcellulose is 1~5:5:2:0.3.
[0008] Preferably, the method for preparing the modified nano-alumina includes the following steps: A. Disperse nano-alumina in ethanol to obtain nano-alumina dispersion. Add oleic acid to the ethanol solution and stir for 30 min. Then slowly add the nano-alumina dispersion and stir at 75~85℃ for 10~12 h. After the reaction is completed, centrifuge, wash and dry to prepare hydrophobic nano-alumina. B. Take hydrophobic nano-alumina and ultrasonically disperse it in deionized water, and stir it at 65~75℃ for 10~15 min to obtain a suspension. Take paraffin and heat it at 65~75℃ until it is completely melted, and then slowly add it to the suspension. Stir it at 65~75℃ for 0.5~1 h. After the reaction is completed, centrifuge, wash and dry to prepare composite nano-alumina. C. Take composite nano-alumina and disperse it in a sodium hydroxide solution with a mass percentage of 2wt%. Stir at room temperature for 1-2 hours. Then wash with deionized water to remove excess sodium hydroxide. Subsequently, add tetrachloromethane to dissolve paraffin. After centrifugation and drying, the modified nano-alumina is prepared.
[0009] Preferably, the preparation of the modified composite filler-based water-reducing agent includes the following steps: I. Add composite filler, 1-ethyl-3-(3-dimethylaminopropyl)-carbodiimide, and N-hydroxysuccinimide to a reactor containing N,N-dimethylformamide. Disperse the mixture evenly by ultrasonication and react at 40-50°C for 1.5-2 hours. Then, centrifuge to remove the supernatant, add deionized water and isopentenyl alcohol polyoxyethylene ether, and react at 40-50°C for 1-4 hours. After the reaction, wash with deionized water and ethanol, recrystallize with ethanol, and vacuum dry to prepare the modified composite filler. II. Take deionized water, modified composite filler and hydrogen peroxide into a reactor, heat and stir. After the temperature rises to 55~60℃, add active monomer A solution and initiator B solution dropwise simultaneously using a constant flow pump. The dropwise addition time is 2~4h. After the dropwise addition is completed, keep the reaction at 55~60℃ for 1~1.5h, and let it cool naturally to 25~30℃. Adjust the pH value of the product to neutral with sodium hydroxide solution, then wash with deionized water and ethanol, dialyze and vacuum dry to prepare the modified composite filler-based water-reducing agent.
[0010] Preferably, the active monomer A solution is acrylic acid and deionized water added in a ratio of 2g:5mL; the initiator B solution is ascorbic acid and deionized water added in a ratio of 0.3g:40mL.
[0011] Preferably, the mass ratio of the deionized water, modified composite filler, hydrogen peroxide, active monomer A solution, and initiator B solution is 3:0.3:0.01:1.4:1.
[0012] Preferably, the preparation of the composite filler in step I includes the following steps: (1) Take the desizing carbon fiber and add it to a mixture of concentrated sulfuric acid and concentrated nitric acid with a volume ratio of 1:1. Place it in a water bath at 65~70℃ for acid oxidation reaction for 4~4.5h. Then take it out and wash it repeatedly with deionized water and anhydrous ethanol until neutral and dry it to prepare oxidized carbon fiber. (2) Prepare a silane hydrolysate by taking anhydrous ethanol, 3-aminopropyltriethoxysilane and deionized water, add carbon dioxide to the silane hydrolysate, disperse it evenly by ultrasonication, and then reflux it at 75~80℃ for 4~4.5h. Then take it out, wash it with deionized water and anhydrous ethanol and dry it to prepare silanized carbon dioxide. (3) Take graphene oxide and ultrasonically disperse it in N,N-dimethylformamide, then add silanized carbon fiber, ultrasonically disperse it evenly, place it in reflux at 100~105℃ for 6~7h, then take it out and wash it with deionized water and anhydrous ethanol and dry it to prepare composite filler.
[0013] The preparation method of the sound-insulating and heat-insulating lightweight building material as described above includes the following steps: weighing each raw material according to the weight parts, pre-mixing cement, fly ash, river sand, quartz sand and deionized water, then adding modified composite filler-based water-reducing agent and foaming agent, preparing samples using concrete sample molds, demolding after the cement has completely solidified, and naturally curing the samples at standard room temperature for 28 days to obtain the sound-insulating and heat-insulating lightweight building material.
[0014] The beneficial effects of this invention are: This invention utilizes the esterification reaction between the carboxyl groups on oleic acid molecules and the hydroxyl groups on the surface of nano-alumina to form chemical bonds. This bonding grafts hydrophobic groups onto the surface of the nano-alumina particles, preparing hydrophobic nano-alumina. Then, after emulsification using the Pickering emulsion method, a sodium hydroxide-induced saponification reaction selectively dissociates the chemical bonds of the hydrophobic nano-alumina, achieving unilateral oleic acid molecule desorption, thus preparing amphiphilic modified nano-alumina. Sodium dodecyl sulfate is used as a foaming agent, and hydroxypropyl methylcellulose, modified nano-alumina, and nano-silica are used as foam stabilizers. The modified nano-alumina... Alumina particles, with their amphiphilic properties, possess excellent interfacial anchoring capabilities, forming a dense adsorption layer at the gas-liquid interface. Through Coulombic interactions, they synergistically construct a composite interfacial film with sodium dodecyl sulfate. Hydroxypropyl methylcellulose forms a secondary barrier through hydrogen bonding and van der Waals forces, while hydroxyl-rich nano-silica particles combine with sodium dodecyl sulfate via electrostatic adsorption to construct a third protective shell, thus forming an ultra-stable foaming agent with a multi-walled core-shell structure. Introducing this foaming agent into foamed concrete achieves synergistic optimization of the mechanical and thermal properties of building materials based on stress dispersion mechanisms and closed-cell thermal insulation effects.
[0015] This invention utilizes concentrated sulfuric acid and concentrated nitric acid to oxidize carbon fibers, introducing hydroxyl and carboxyl functional groups onto the carbon fiber surface to enhance its surface activity. Then, 3-aminopropyltriethoxysilane is used as a "bridging agent" to graft graphene oxide onto the oxidized carbon fibers, preparing a composite filler. This achieves reinforcement by combining two-dimensional nanoscale graphene oxide with one-dimensional micron-scale carbon fibers. Furthermore, the graphene oxide on the surface of the composite filler improves the mechanical bonding force between the carbon fibers and the concrete matrix and promotes the formation of hydration products on the composite filler surface. Finally, isopentenyl alcohol polyoxyethylene... In-situ esterification modification of composite fillers with ethers yields modified composite fillers. These modified composite fillers exhibit superior dispersion within the matrix due to the steric hindrance of isopentenyl alcohol polyoxyethylene ether, enabling them to uniformly fill the pores of the matrix material. Furthermore, the active double bonds of isopentenyl alcohol polyoxyethylene ether introduced into the modified composite filler can be copolymerized with acrylic acid via free radical polymerization to prepare a modified composite filler-based water-reducing agent. This agent is then used for dispersion and reinforcement in concrete systems. The composite filler exhibits excellent bonding between the composite filler and the concrete matrix interface, demonstrating superior mechanical properties. Detailed Implementation
[0016] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.
[0017] Example 1: Preparation of a foaming agent includes the following steps: Take 3g of modified nano-alumina, 5g of nano-silica and 2g of sodium dodecyl sulfate and add them to 80mL of deionized water. Sonicate at room temperature for 30min to obtain a mixture. Take 0.3g of hydroxypropyl methylcellulose and dissolve it in 10mL of deionized water. Stir at 500rpm for 30min at 50℃ and then add it to the mixture. Add calcium hydroxide to adjust the pH of the system to 9 and continue stirring at 500rpm for 2h to obtain a foaming agent solution. Then let the foaming agent solution stand at room temperature for 24h and use a foaming machine to generate foaming agent by compressed air.
[0018] The preparation of modified nano-alumina includes the following steps: A. Take 2g of nano-alumina and disperse it in 100mL of ethanol to obtain nano-alumina dispersion. Take 6g of oleic acid and add it to 200mL of ethanol solution. Stir for 30min, then slowly add the nano-alumina dispersion. Place it at 80℃ and stir at 600rpm for 12h. After the reaction is completed, centrifuge, wash and dry to prepare hydrophobic nano-alumina. B. Take 2g of hydrophobic nano-alumina and ultrasonically disperse it in 100mL of deionized water. Stir at 500rpm for 15min at 70℃ to obtain a suspension. Heat paraffin at 70℃ until it is completely melted. Then slowly add it to the suspension and stir at 1200rpm for 0.5h at 70℃. After the reaction is completed, centrifuge, wash and dry to prepare composite nano-alumina. C. Take 3g of composite nano alumina and disperse it in 100mL of sodium hydroxide solution with a mass percentage of 2wt%. Stir at 400rpm for 1.5h at room temperature. Then wash with deionized water to remove excess sodium hydroxide. Then add 50mL of tetrachloromethane to dissolve paraffin. After centrifugation and drying, the modified nano alumina is prepared.
[0019] Example 2: Preparation of a modified composite filler-based water-reducing agent includes the following steps: I. Add 0.5g of composite filler, 0.05g of 1-ethyl-3-(3-dimethylaminopropyl)-carbodiimide, and 0.01g of N-hydroxysuccinimide to a reactor containing 100mL of N,N-dimethylformamide. Disperse the mixture evenly by ultrasonication and react at 45℃ for 2h. Then, centrifuge to remove the supernatant, add 100mL of deionized water and 50g of isopentenyl alcohol polyoxyethylene ether, and react at 45℃ for 3h. After the reaction, wash with deionized water and ethanol, recrystallize with ethanol, and vacuum dry to prepare the modified composite filler. II. Take 120 mL of deionized water, 12 g of modified composite filler and 0.4 g of hydrogen peroxide into a reactor, heat and stir. After the temperature rises to 60 °C, add the active monomer A solution (16 g of acrylic acid and 40 mL of deionized water) and the initiator B solution (0.3 g of ascorbic acid and 40 mL of deionized water) dropwise simultaneously using a constant flow pump. The dropwise addition time is 3 h. After the dropwise addition is completed, keep the reaction at 60 °C for 1 h, and let it cool naturally to 30 °C. Adjust the pH value of the product to neutral with sodium hydroxide solution, then wash with deionized water and ethanol, dialyze (with the relative molecular mass cutoff higher than 5000 g / mol), and then vacuum dry to prepare the modified composite filler-based water-reducing agent.
[0020] The preparation of the composite filler includes the following steps: (1) Take the desizing carbon fiber and add it to 1500 mL of a mixture of concentrated sulfuric acid and concentrated nitric acid with a volume ratio of 1:1. Place it in a 70°C water bath for acid oxidation reaction for 4 h. Then take it out and wash it repeatedly with deionized water and anhydrous ethanol until neutral and dry it to prepare oxidized carbon fiber. (2) Prepare a silane hydrolysate by taking 1500 mL of anhydrous ethanol, 350 mL of 3-aminopropyltriethoxysilane and 142 mL of deionized water. Add the oxidized carbon fiber to the silane hydrolysate, disperse it evenly by ultrasonication, and then reflux it at 80 °C for 4 h. After that, take it out, shake and wash it with deionized water and anhydrous ethanol and dry it to prepare silanized carbon fiber. (3) Take 30g of graphene oxide and ultrasonically disperse it in 3900mL of N,N-dimethylformamide. Then add 30g of silanized carbon fiber, ultrasonically disperse it evenly, and reflux it at 105℃ for 6h. Then take it out, shake and wash it with deionized water and anhydrous ethanol, and dry it to prepare the composite filler.
[0021] Example 3 A sound-insulating and heat-insulating lightweight building material, comprising the following raw materials in parts by weight: 100 parts of P·O42.5 grade ordinary silicate cement, 14 parts of fly ash, 5.5 parts of river sand, 5.3 parts of quartz sand, 4.2 parts of foaming agent prepared in Example 1, 1.3 parts of modified composite filler-based water-reducing agent prepared in Example 2, and 48 parts of deionized water.
[0022] The preparation method of the above-mentioned sound-insulating and heat-insulating lightweight building material includes the following steps: weigh each raw material according to the weight parts, pre-mix cement, fly ash, river sand, quartz sand and deionized water, then add modified composite filler-based water-reducing agent and foaming agent, prepare the sample using a concrete sample mold, demold after the cement has completely solidified, and place the sample at standard room temperature for natural curing for 28 days to obtain the sound-insulating and heat-insulating lightweight building material.
[0023] Example 4 A sound-insulating and heat-insulating lightweight building material, comprising the following raw materials in parts by weight: 100 parts of P·O42.5 grade ordinary silicate cement, 20 parts of fly ash, 7.7 parts of river sand, 7.2 parts of quartz sand, 5.5 parts of foaming agent prepared in Example 1, 3.6 parts of modified composite filler-based water-reducing agent prepared in Example 2, and 54 parts of deionized water.
[0024] The preparation method of the above-mentioned sound-insulating and heat-insulating lightweight building material is the same as that in Example 3.
[0025] Example 5 A sound-insulating and heat-insulating lightweight building material, comprising the following raw materials in parts by weight: 100 parts of P·O42.5 grade ordinary silicate cement, 24 parts of fly ash, 9.3 parts of river sand, 9.2 parts of quartz sand, 6.6 parts of foaming agent prepared in Example 1, 4.7 parts of modified composite filler-based water-reducing agent prepared in Example 2, and 58 parts of deionized water.
[0026] The preparation method of the above-mentioned sound-insulating and heat-insulating lightweight building material is the same as that in Example 3.
[0027] Comparative Example 1: The preparation of a foaming agent includes the following steps: Take 3g of nano-alumina, 5g of nano-silica and 2g of sodium dodecyl sulfate and add them to 80mL of deionized water. Sonicate at room temperature for 30min to obtain a mixture. Take 0.3g of hydroxypropyl methylcellulose and dissolve it in 10mL of deionized water. Stir at 500rpm for 30min at 50℃ and then add it to the mixture. Add calcium hydroxide to adjust the pH of the system to 9 and continue stirring at 500rpm for 2h to obtain a foaming agent solution. Then let the foaming agent solution stand at room temperature for 24h and use a foaming machine to generate foaming agent by compressed air.
[0028] Comparative Example 2: The preparation of a foaming agent includes the following steps: Take 3g of the hydrophobic nano-alumina prepared in Example 1, 5g of nano-silica and 2g of sodium dodecyl sulfate and add them to 80mL of deionized water. Sonicate at room temperature for 30min to obtain a mixture. Take 0.3g of hydroxypropyl methylcellulose and dissolve it in 10mL of deionized water. Stir at 500rpm for 30min at 50℃ and then add it to the mixture. Add calcium hydroxide to adjust the pH of the system to 9 and continue stirring at 500rpm for 2h to obtain a foaming agent solution. Then let the foaming agent solution stand at room temperature for 24h and use a foaming machine to generate foaming agent by compressed air.
[0029] Comparative Example 3: Preparation of a modified composite filler-based water-reducing agent includes the following steps: I. Add 0.5g of graphene oxide, 0.05g of 1-ethyl-3-(3-dimethylaminopropyl)-carbodiimide, and 0.01g of N-hydroxysuccinimide to a reactor containing 100mL of N,N-dimethylformamide. Disperse the mixture evenly by ultrasonication and react at 45℃ for 2h. Then, centrifuge to remove the supernatant, add 100mL of deionized water and 50g of isopentenyl alcohol polyoxyethylene ether, and react at 45℃ for 3h. After the reaction, wash with deionized water and ethanol, recrystallize with ethanol, and vacuum dry to prepare the modified composite filler. II. Take 120 mL of deionized water, 12 g of modified composite filler and 0.4 g of hydrogen peroxide into a reactor, heat and stir. After the temperature rises to 60 °C, add the active monomer A solution (16 g of acrylic acid and 40 mL of deionized water) and the initiator B solution (0.3 g of ascorbic acid and 40 mL of deionized water) dropwise simultaneously using a constant flow pump. The dropwise addition time is 3 h. After the dropwise addition is completed, keep the reaction at 60 °C for 1 h, and let it cool naturally to 30 °C. Adjust the pH value of the product to neutral with sodium hydroxide solution, then wash with deionized water and ethanol, dialyze (with the relative molecular mass cutoff higher than 5000 g / mol), and then vacuum dry to prepare the modified composite filler-based water-reducing agent.
[0030] Comparative Example 4: A sound-insulating and heat-insulating lightweight building material, comprising the following raw materials in parts by weight: 100 parts of P·O42.5 grade ordinary silicate cement, 24 parts of fly ash, 9.3 parts of river sand, 9.2 parts of quartz sand, 6.6 parts of foaming agent prepared in Comparative Example 1, 4.7 parts of modified composite filler-based water-reducing agent prepared in Example 2, and 58 parts of deionized water.
[0031] The preparation method of the above-mentioned sound-insulating and heat-insulating lightweight building material is the same as that in Example 3.
[0032] Comparative Example 5: A sound-insulating and heat-insulating lightweight building material, comprising the following raw materials in parts by weight: 100 parts of P·O42.5 grade ordinary silicate cement, 24 parts of fly ash, 9.3 parts of river sand, 9.2 parts of quartz sand, 6.6 parts of foaming agent prepared in Comparative Example 2, 4.7 parts of modified composite filler-based water-reducing agent prepared in Example 2, and 58 parts of deionized water.
[0033] The preparation method of the above-mentioned sound-insulating and heat-insulating lightweight building material is the same as that in Example 3.
[0034] Comparative Example 6: A sound-insulating and heat-insulating lightweight building material, comprising the following raw materials in parts by weight: 100 parts of P·O42.5 grade ordinary silicate cement, 24 parts of fly ash, 9.3 parts of river sand, 9.2 parts of quartz sand, 6.6 parts of foaming agent prepared in Example 1, 4.7 parts of modified composite filler-based water-reducing agent prepared in Comparative Example 3, and 58 parts of deionized water.
[0035] The preparation method of the above-mentioned sound-insulating and heat-insulating lightweight building material is the same as that in Example 3.
[0036] Comparative Example 7: A sound-insulating and heat-insulating lightweight building material, comprising the following raw materials in parts by weight: 100 parts of P·O42.5 grade ordinary silicate cement, 24 parts of fly ash, 9.3 parts of river sand, 9.2 parts of quartz sand, 6.6 parts of foaming agent prepared in Example 1, 2.4 parts of composite filler prepared in Example 2, 2.3 parts of commercially available polycarboxylate high-performance water-reducing agent (water reduction rate of 27%), and 58 parts of deionized water.
[0037] The preparation method of the above-mentioned sound-insulating and heat-insulating lightweight building material is the same as that in Example 3.
[0038] Performance testing The lightweight building materials prepared in Examples 3-5 and Comparative Examples 4-7 were subjected to performance testing: (1) Compressive and flexural strength tests: The compressive strength of a lightweight building material specimen with a size of 100mm×100mm×100mm was tested using a fully automatic cement pressure testing machine; the flexural strength was tested using a three-point bending testing machine on a lightweight building material specimen with a size of 40mm×40mm×160mm. The loading rates for the compressive and flexural strength tests were controlled at 2.0±0.5kN / s and 0.2±0.05kN / s, respectively. The data results are shown in Table 1.
[0039] (2) Water absorption rate test: The test block was dried at 60℃, then weighed according to the standard of "Foamed Concrete" (JG / T266-2011), and soaked for 3 days. Finally, the water absorption rate of the test block was calculated, and the data results are shown in Table 1.
[0040] (3) Thermal insulation performance test: The thermal insulation performance of the sample was tested using a thermal conductivity tester, and the data results are shown in Table 1.
[0041] Table 1 Sample performance test results
[0042] As shown in Table 1, the lightweight building materials prepared in Examples 3-5 of this invention have high compressive and flexural strengths, low water absorption, and good thermal insulation performance. In Comparative Example 4, the foaming agent added did not modify the nano-alumina. In Comparative Example 5, the modified nano-alumina was replaced with an equal amount of hydrophobic nano-alumina. The measured compressive and flexural strengths in Comparative Examples 4-5 were lower than those in Examples 3-5, while the water absorption and thermal conductivity were higher. This indicates that adding modified nano-alumina to the foaming agent of foamed concrete effectively improves the mechanical properties, impermeability, and thermal insulation performance of the material due to the strong load-bearing capacity, water resistance, and thermal insulation capacity of the multi-walled core-shell structure. In Comparative Example 6, the composite filler was replaced with an equal amount of graphene oxide, and the measured compressive strength... The strength and flexural strength were lower than those of Examples 3-5, indicating that the mechanical properties can be enhanced by tightly binding carbon fibers and graphene oxide through chemical bonds. In Comparative Example 7, the composite filler and commercially available polycarboxylate superplasticizer were simply mixed. The measured mechanical properties and impermeability were slightly lower than those of Examples 3-5. This is because grafting polycarboxylate superplasticizer onto the surface of the composite filler can increase the dispersibility of the composite filler, allowing it to fill the pores of the matrix material uniformly. Furthermore, the macromolecular polymer on the surface of the composite filler can entangle with the hydration products of the matrix, optimizing the internal structure of the matrix material, thereby enhancing the mechanical strength and impermeability.
[0043] In the description of this specification, references to terms such as "an embodiment," "example," "specific example," etc., indicate that a specific feature, structure, material, or characteristic described in connection with that embodiment or example is included in at least one embodiment or example of the invention. In this specification, illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples.
[0044] The foregoing has shown and described the basic principles, main features, and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The embodiments and descriptions in the specification are merely illustrative of the principles of the invention. Various changes and modifications can be made to the invention without departing from its spirit and scope, and all such changes and modifications fall within the scope of the claimed invention.
Claims
1. A sound-insulating and heat-insulating lightweight building material, characterized in that, The raw materials include the following parts by weight: 100 parts cement, 12-25 parts fly ash, 5-10 parts river sand, 5-10 parts quartz sand, 4-7 parts foaming agent, 1-5 parts modified composite filler-based water-reducing agent, and 45-60 parts deionized water. The foaming agent is made using sodium dodecyl sulfate as a foaming agent and hydroxypropyl methylcellulose, modified nano-alumina, and nano-silica as foam stabilizers. The modified nano-alumina is prepared by esterification of oleic acid with nano-alumina to form chemical bonds, resulting in hydrophobic nano-alumina. After emulsification using the Pickering emulsion method, the chemical bonds of the hydrophobic nano-alumina are selectively dissociated by a sodium hydroxide-induced saponification reaction, achieving desorption of oleic acid molecules on one side. The modified composite filler-based water-reducing agent is prepared by in-situ esterification modification of the composite filler with isopentenyl alcohol polyoxyethylene ether, and then the prepared modified composite filler is prepared by free radical copolymerization reaction with acrylic acid; the composite filler is prepared by oxidizing carbon fiber with concentrated sulfuric acid and concentrated nitric acid to prepare oxidized carbon fiber, and then grafting graphene oxide and oxidized carbon fiber with 3-aminopropyltriethoxysilane as "bridging agent".
2. The sound-insulating and heat-insulating lightweight building material according to claim 1, characterized in that, The cement is P·O42.5 grade ordinary Portland cement; the fineness modulus of the river sand is between 2.4 and 2.8; and the particle size of the quartz sand is 100 to 210 µm.
3. The sound-insulating and heat-insulating lightweight building material according to claim 1, characterized in that, The preparation of the foaming agent includes the following steps: Modified nano-alumina, nano-silica, and sodium dodecyl sulfate were added to deionized water and sonicated at room temperature for 30 min to obtain a mixture. Hydroxypropyl methylcellulose was dissolved in deionized water and stirred at 500 rpm for 30 min at 50 °C. The solution was then added to the mixture, and calcium hydroxide was added to adjust the pH of the system to 9. The mixture was stirred at 500 rpm for 2 h to obtain a foaming agent solution. The foaming agent solution was then allowed to stand at room temperature for 24 h, and a foaming machine was used to generate a foaming agent using compressed air.
4. The sound-insulating and heat-insulating lightweight building material according to claim 3, characterized in that, The mass ratio of the modified nano-alumina, nano-silica, sodium dodecyl sulfate, and hydroxypropyl methylcellulose is 1~5:5:2:0.
3.
5. The sound-insulating and heat-insulating lightweight building material according to claim 3, characterized in that, The preparation method of the modified nano-alumina includes the following steps: A. Disperse nano-alumina in ethanol to obtain nano-alumina dispersion. Add oleic acid to the ethanol solution and stir for 30 min. Then slowly add the nano-alumina dispersion and stir at 75~85℃ for 10~12 h. After the reaction is completed, centrifuge, wash and dry to prepare hydrophobic nano-alumina. B. Take hydrophobic nano-alumina and ultrasonically disperse it in deionized water, and stir it at 65~75℃ for 10~15 min to obtain a suspension. Take paraffin and heat it at 65~75℃ until it is completely melted, and then slowly add it to the suspension. Stir it at 65~75℃ for 0.5~1 h. After the reaction is completed, centrifuge, wash and dry to prepare composite nano-alumina. C. Take composite nano-alumina and disperse it in a sodium hydroxide solution with a mass percentage of 2wt%. Stir at room temperature for 1-2 hours. Then wash with deionized water to remove excess sodium hydroxide. Subsequently, add tetrachloromethane to dissolve paraffin. After centrifugation and drying, the modified nano-alumina is prepared.
6. The sound-insulating and heat-insulating lightweight building material according to claim 1, characterized in that, The preparation of the modified composite filler-based water-reducing agent includes the following steps: I. Add composite filler, 1-ethyl-3-(3-dimethylaminopropyl)-carbodiimide, and N-hydroxysuccinimide to a reactor containing N,N-dimethylformamide. Disperse the mixture evenly by ultrasonication and react at 40-50°C for 1.5-2 hours. Then, centrifuge to remove the supernatant, add deionized water and isopentenyl alcohol polyoxyethylene ether, and react at 40-50°C for 1-4 hours. After the reaction is complete, wash with deionized water and ethanol, recrystallize with ethanol, and vacuum dry to prepare the modified composite filler. II. Take deionized water, modified composite filler and hydrogen peroxide into a reactor, heat and stir. After the temperature rises to 55~60℃, add active monomer A solution and initiator B solution dropwise simultaneously using a constant flow pump. The dropwise addition time is 2~4h. After the dropwise addition is completed, keep the reaction at 55~60℃ for 1~1.5h, and let it cool naturally to 25~30℃. Adjust the pH value of the product to neutral with sodium hydroxide solution, then wash with deionized water and ethanol, dialyze and vacuum dry to prepare the modified composite filler-based water-reducing agent.
7. The sound-insulating and heat-insulating lightweight building material according to claim 6, characterized in that, The active monomer A solution is an addition ratio of 2g:5mL of acrylic acid and deionized water; the initiator B solution is an addition ratio of 0.3g:40mL of ascorbic acid and deionized water.
8. The sound-insulating and heat-insulating lightweight building material according to claim 6, characterized in that, The mass ratio of the deionized water, modified composite filler, hydrogen peroxide, active monomer A solution, and initiator B solution is 3:0.3:0.01:1.4:
1.
9. The sound-insulating and heat-insulating lightweight building material according to claim 6, characterized in that, The preparation of the composite filler in step I includes the following steps: (1) Take the desizing carbon fiber and add it to a mixture of concentrated sulfuric acid and concentrated nitric acid with a volume ratio of 1:
1. Place it in a water bath at 65~70℃ for acid oxidation reaction for 4~4.5h. Then take it out and wash it repeatedly with deionized water and anhydrous ethanol until neutral and dry it to prepare oxidized carbon fiber. (2) Prepare a silane hydrolysate by taking anhydrous ethanol, 3-aminopropyltriethoxysilane and deionized water, add carbon dioxide to the silane hydrolysate, disperse it evenly by ultrasonication, and then reflux it at 75~80℃ for 4~4.5h. Then take it out, wash it with deionized water and anhydrous ethanol and dry it to prepare silanized carbon dioxide. (3) Take graphene oxide and ultrasonically disperse it in N,N-dimethylformamide, then add silanized carbon fiber, ultrasonically disperse it evenly, place it in reflux at 100~105℃ for 6~7h, then take it out and wash it with deionized water and anhydrous ethanol and dry it to prepare composite filler.
10. A method for preparing a sound-insulating and heat-insulating lightweight building material according to any one of claims 1 to 9, characterized in that, The process includes the following steps: weighing each raw material according to weight, pre-mixing cement, fly ash, river sand, quartz sand and deionized water, then adding modified composite filler-based water-reducing agent and foaming agent, preparing samples using concrete sample molds, demolding after the cement has completely solidified, and naturally curing the samples at standard room temperature for 28 days to obtain sound-insulating and heat-insulating lightweight building materials.
Citation Information
Patent Citations
Wear resistant and antistatic polyamide composite material and preparation method thereof
CN106967293A
Amphiphilic Janus nano particle and preparation method and application thereof
CN111303853A